Risk Factors of Hypercholesterolemia on Obese Pre-elderly Population in Rejosari Sub-village Gunung Kidul Yogyakarta - Desto Arisandi; Yesi Apriliasari; Subrata Tri Widada (Journal of Health (JoH), 2016)
Background: Obesity is one of the most epidemiological burden which is being a dangerous threat for global health. It also contributes for leading cause of hypercholesterolemia. Prevalence of stroke, diabetes mellitus, coronary heart disease, and hypertension in Indonesia has reached out 23.7% in 2007. Rejosari sub-village, Kemadang village, Tanjungsari sub-district locate in coastal area which is fisher taking mostly part of the citizen's occupation. Hence they have tendency to intake sea products such as shrimps, squids, crabs, anchovies, and bivalves that contain amino acid required to growth and cell recovery nevertheless it also has much cholesterol contained which cause of total cholesterol level rising. The aims of this study to determine risk factors of hypercholesterolemia on obese pre-eldery population in Rejosari sub-village, Kemadang village, Tanjungsari sub-district, Gunung Kidul district, Yogyakarta. Method: This was an analytic observational study with cross sectional that conducted on February 2015 on obese pre-eldery population in Rejosari sub-village, Kemadang village, Tanjungsari sub-district, Gunung Kidul district, Yogyakarta. Data collected such age, sex, blood pressure, seafood intake frequencies, and total cholesterol. Data were analyzed by STATA version 12 software for windows with spearman correlation statistical test. Result: This study findings that 30 pre-elderly people came as respondents. Data performed the average value of age was 49 years old, systolic blood pressure was 142 mmHg, diastolic blood pressure was 87 mmHg, seafood intake frequencies was 3 times per week, and total cholesterol level was 241 mg/dl. Spearman correlation shown age (p value=0.0477), systolic blood pressure (p value=0.0012), diasolic blood pressure (p value= 0.0435) and seafood intake frequencies (p value= 0.0018) have stattistical correlation with hypercholesterolemia. Conclusion:Age, systolic blood pressure, diastolic blood pressure, and seafood intake frequencies are correlated with total cholesterol raising within blood.